2013
DOI: 10.1063/1.4793505
|View full text |Cite
|
Sign up to set email alerts
|

Electronic states of thiophene/phenylene co-oligomers: Extreme-ultra violet excited photoelectron spectroscopy observations and density functional theory calculations

Abstract: We have investigated electronic states in the valence electron bands for the thin films of three thiophene/phenylene co-oligomer (TPCO) compounds, 2,5-bis(4-biphenylyl)thiophene (BP1T), 1,4-bis(5-phenylthiophen-2-yl)benzene (AC5), and 1,4-bis{5-[4-(trifluoromethyl)phenyl]thiophen-2-yl}benzene (AC5-CF3), by using extreme-UV excited photoelectron spectroscopy (EUPS). By comparing both EUPS spectra and secondary electron spectra between AC5 and AC5-CF3, we confirm that CF3 substitution to AC5 deepens valence stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
0
8
0
6
Order By: Relevance
“…Yamao et al have confirmed the n‐type conduction from a light‐emitting FET device with vapor‐grown crystals of 1,4‐bis{5‐[4‐(trifluoromethyl)phenyl]thiophen‐2‐yl}benzene (AC5‐CF 3 ) . By introducing trifluoromethyl groups, the HOMO/LUMO energies of AC5‐CF 3 are deepened by 0.35 and 0.41 eV, respectively, in comparison to those of unsubstituted AC5 as demonstrated by the density functional theory (DFT) calculations . In this study, we chose substitution into BP1T with cyano groups which are stronger electron‐withdrawing than trifluoromethyl groups .…”
mentioning
confidence: 91%
“…Yamao et al have confirmed the n‐type conduction from a light‐emitting FET device with vapor‐grown crystals of 1,4‐bis{5‐[4‐(trifluoromethyl)phenyl]thiophen‐2‐yl}benzene (AC5‐CF 3 ) . By introducing trifluoromethyl groups, the HOMO/LUMO energies of AC5‐CF 3 are deepened by 0.35 and 0.41 eV, respectively, in comparison to those of unsubstituted AC5 as demonstrated by the density functional theory (DFT) calculations . In this study, we chose substitution into BP1T with cyano groups which are stronger electron‐withdrawing than trifluoromethyl groups .…”
mentioning
confidence: 91%
“…Для установления π * или σ * характера наблюдаемых ТССПТ максимумов по-требовались бы дополнительные сведения, полученные из теоретических расчетов электронной структуры в об-ласти зоны проводимости или из результатов NEXAFS исследований пленок СH 3 −PTTP−СH 3 . В литературе имеются сведения о плотности электронных состояний валентной энергетической зоны пленок на основе неко-торых молекул ТФСО [15], а публикаций исследований электронной структуры зоны проводимости обнаружено не было. Поэтому для оценки характера максимумов H 1 −H 6 (рис.…”
Section: результаты и обсуждениеunclassified
“…Уменьшение величины E vac −E F , значения работы выхода поверхности, соответствует переносу отрицательного за-ряда из органической пленки в подложку. В литературе имеются данные по значениям работы выхода пленок на основе некоторых ТФСО [15], достаточно близких по структуре к исследованным в данной работе пленкам СH 3 −PTTP−СH 3 . Так, значения работы выхода незаме-щенных молекул ТФСО, а именно молекул 1,4-bis(5-phenylthiophen-2-yl)benzene, составили около 4 eV [15], т. е. практически не отличаются от установленных нами значений E vac −E F пленок СH 3 −PTTP−СH 3 .…”
Section: результаты и обсуждениеunclassified
See 1 more Smart Citation
“…A laser-produced plasma (LPP) emits strong short wavelength radiation and finds many applications such as x-ray shadowgraphy of dense laser-imploded plasma, 1 x-ray laser, 2 x-ray microscopy of living cells, 3 extreme ultraviolet (EUV) lithography, 4 actinic inspection of phase defects in EUV mask blank, 5 photoelectron spectroscopy for observing electronic states of the topmost atomic layer of materials, 6,7 and so on. Requirements for an LPP are totally different in each application.…”
Section: Introductionmentioning
confidence: 99%